Making African agriculture and food systems work for nutrition: What has been done, and what needs to be done? - Gillespie, Stuart; Dufour, Charlotte (International Food Policy Research Institute, 2016)
The food and agriculture sector is pivotal not only to addressing undernutrition but also to containing and preventing the spread of diet-related noncommunicable disease. This context requires action throughout the food system, from sustainably managing natural resources and input supplies to enabling consumption of healthy diets and promoting gender equity. Political commitment is growing, but much remains to be done in terms of strengthening the information base to support strategic decision making, and developing capacities for implementation at scale. In April 2016, the UN General Assembly enacted a Decade of Action for Nutrition, and nutrition is directly or indirectly related to all of the Sustainable Development Goals. This enabling environment at the global level should foster further progress in the region, and conversely, African countries can inspire other regions of the world by pursuing innovative approaches for unleashing the latent potential of the agrifood sector to drive positive change in nutrition.